Aplicabilidade do conceito de universidade corporativa ao Sistema Federação das Indústrias do Estado do Paraná na visão dos gestores: um estudo empírico - Baglioli Filho, Raul (2002)
Due to the globalization of markets and of production as well as to the wilderness of market disputation, to the accelerated scientific, tecnological and social transformation and the dawning of the economy based on knowledge, the organizations are permanently being defied to develop new competences, in order to create sustainable competitive advantages. By these means, they are installing their own learning infra-structures, in order to provide the development and continued education to their employees, focused on the essencial needings of the organization, ali along with the strategy of their business - the so called Corporate Universities. The application of the concept of Corporate University to an organization, requires the existence of an enterprise ambience, prepared to develop a permanent learning culture. Essencial facto r in this process is the commitment of the organization managers, whose role is that of the construction of the learning ambience, creating room and channels to the exercise of collective construction with new knowledges and organization practices. This study intends to verify the applicability of the refered concept to the 'Sistema Federação das Indústrias do Estado do Paraná', making use of the Institution managers as subjects of analysis, and the 'método distanciai' for data analysis. The levei of satisfaction of the indicators used in the research applied to the managers, infers that they evaluate that there exists in the 'sistema FIEP' a predisposed organizational ambience to the appl ication of the concept of Corporate University.